The commercial use of digital media to market alcohol products: a narrative review. (11th October 2016) - Lobstein, Tim; Landon, Jane; Thornton, Nicole; Jernigan, David
Abstract: Background and aims: The rising use of digital media in the last decade, including social networking media and downloadable applications, has created new opportunities for marketing a wide range of goods and services, including alcohol products. This paper aims to review the evidence in order to answer a series of policy‐relevant questions: does alcohol marketing through digital media influence drinking behaviour or increases consumption; what methods of promotional marketing are used, and to what extent; and what is the evidence of marketing code violations and especially of marketing to children? Method and findings: A search of scientific, medical and social journals and authoritative grey literature identified 47 relevant papers (including 14 grey literature documents). The evidence indicated (i) that exposure to marketing through digital media was associated with higher levels of drinking behaviour; (ii) that the marketing activities make use of materials and approaches that are attractive to young people and encourage interactive engagement with branded messaging; and (iii) there is evidence that current alcohol marketing codes are being undermined by alcohol producers using digital media. Conclusions: There is evidence to support public health interventions to restrict the commercial promotion of alcohol in digital media, especially measures to protect children and youth.